Intergroup contact and collective action: an integrative approach - Cakal, H (2013)
This thesis investigated the effects of intergroup contact on different types of collective action tendencies among advantaged and disadvantaged groups. Studies 1 and 2 tested the simultaneous effects of intergroup contact and established predictors of collective action on collective action tendencies and ingroup and outgroup oriented policies among Blacks and Whites in South Africa, and compared the effects of intergroup contact and social identity on collective action tendencies via relative deprivation and group efficacy. The findings revealed that while social identity was positively associated with collective action tendencies, both directly and indirectly, effects of contact were negative and indirect via relative deprivation and group efficacy. Studies 3 and 4 investigated the effects of contact and social identity on collective action tendencies via perceived threats. Using data from Turkish and Kurdish groups in Turkey, I found that social identity predicted collective action tendencies positively, both directly and indirectly, while it predicted outgroup attitudes negatively and indirectly via perceived threats. Intergroup contact, on the other hand, predicted outgroup attitudes positively, both directly and indirectly, and collective action tendencies negatively via perceived threats. In Study 5, intergroup contact was positively associated, both directly and indirectly, via perspective taking and collective guilt, associated with outgroup oriented collective action tendencies. In Study 6, the effect of social identity on ingroup oriented collective action was positive and direct. Intergroup contact with the weaker minority group, on the other hand, was positively associated with outgroup oriented collective action tendencies via perspective taking. Additionally, intergroup contact with the majority outgroup moderated this relationship. When participants reported more contact with the majority group, intergroup contact with the weaker minority was not associated with outgroup oriented collective action tendencies. However, when the participants reported less contact with the majority group, intergroup contact positively predicted outgroup oriented collective action tendencies. Finally, Study 7 investigated the effects of two different dimensions of contact, contact with the majority and minority on collective action, via outgroup attitudes, dual-identification, and common ingroup identity in a three wave longitudinal design (N=610) among Turkish Cypriots in northern Cyprus. While the results did not support findings from the previous studies on the so-called paradoxical effects of contact on collective action tendencies, they revealed a robust negative reciprocal relationship between outgroup attitudes toward Greek Cypriots and collective action tendencies.